Leucine-Enriched Essential Amino Acids Enhance the Antiseizure Effects of the Ketogenic Diet in Rats - Takeuchi, Fumika; Nishikata, Natsumi; Nishimura, Mai; Nagao, Kenji; Kawamura, Masahito (Frontiers in Neuroscience, 2021)
The classic ketogenic diet (KD) can be used successfully to treat medically refractory epilepsy. However, the KD reduces seizures in 50–70% of patients with medically refractory epilepsy, and its antiseizure effect is limited. In the current study, we developed a new modified KD containing leucine (Leu)-enriched essential amino acids. Compared with a normal KD, the Leu-enriched essential amino acid-supplemented KD did not change the levels of ketosis and glucose but enhanced the inhibition of bicuculline-induced seizure-like bursting in extracellular recordings of acute hippocampal slices from rats. The enhancement of antiseizure effects induced by the addition of Leu-enriched essential amino acids to the KD was almost completely suppressed by a selective antagonist of adenosine A1 receptors or a selective dose of pannexin channel blocker. The addition of Leu-enriched essential amino acids to a normal diet did not induce any antiseizure effects. These findings indicate that the enhancement of the antiseizure effects of the KD is mediated by the pannexin channel-adenosine A1 receptor pathway. We also analyzed amino acid profiles in the plasma and hippocampus. A normal KD altered the levels of many amino acids in both the plasma and hippocampus. The addition of Leu-enriched essential amino acids to a KD further increased and decreased the levels of several amino acids, such as threonine, histidine, and serine, suggesting that altered metabolism and utilization of amino acids may play a role in its antiseizure effects. A KD supplemented with Leu-enriched essential amino acids may be a new therapeutic option for patients with epilepsy, including medically refractory epilepsy.